2018
DOI: 10.1097/rnj.0000000000000129
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Needs of Family Caregivers of Stroke Patients During Inpatient Rehabilitation Using Interview, Art, and Survey

Abstract: The purpose of this study is to explore the needs of family members at the bedside of stroke patients (n = 12) admitted to an inpatient rehabilitation facility (IRF). Family members' needs were determined through semistructured interviews, "Draw a Bridge" art therapy technique, and the Family Inventory of Needs. Family members described a family-centered approach to care that addressed the following needs: assistance with preparing for discharge, staff caring for family members, communication about the plan of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 10 publications
4
33
0
Order By: Relevance
“…They, like us, found that it is often not easy to access the needed information and that the searching process often leads to frustration. The need for information is also described by Camicia et al, 33 who found that "consistency" was a key to eventually being able to hear and understand what was being said. Relatives in this study stated that they felt disappointed that the health care professionals did not take more responsibility in terms of involving and informing them; they said that, had these information needs been met, they would have felt less anxious and more confident.…”
Section: Discussionmentioning
confidence: 87%
“…They, like us, found that it is often not easy to access the needed information and that the searching process often leads to frustration. The need for information is also described by Camicia et al, 33 who found that "consistency" was a key to eventually being able to hear and understand what was being said. Relatives in this study stated that they felt disappointed that the health care professionals did not take more responsibility in terms of involving and informing them; they said that, had these information needs been met, they would have felt less anxious and more confident.…”
Section: Discussionmentioning
confidence: 87%
“…Psychotherapy is a therapeutic method that aims to improve the human by examining feelings, attitudes, ways of thinking, and how the individual behaves. The types of psychotherapy applied to psychosocial caregiver problems include thought-stopping therapy, cognitive therapy, progressive muscle relaxation therapy, and psychoeducation therapy [19]. The purpose of psychoeducation on caregivers is to increase understanding of family members to disease journey, reduce recurrence of stroke, and increase family and client roles [20].…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is a leading cause of lifelong functional disability that limits the activities of daily living of stroke survivors worldwide [1,2]. Due to the sudden-onset nature of strokes, families are faced with a situation where they have to take care of the patient themselves without being fully prepared [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Res. Public Health 2021, 18, 2960 2 of 10 reported feeling emotionally drained, anxious, uncertain, and apprehensive, practicing unhealthy habits and anticipating challenges during the transition from rehabilitation to home [1]. Caregiving was interpreted as suffering, an obligation, a personal choice, a meaningful opportunity, and a natural part of living in Chinese family caregivers of stroke survivors [13].…”
Section: Introductionmentioning
confidence: 99%